Identification of eight novel SDHB, SDHC, SDHD germline variants in Danish pheochromocytoma/paraganglioma patients. Issue 1 (December 2016) - Bennedbæk, Marc; Rossing, Maria; Rasmussen, Åse; Gerdes, Anne-Marie; Skytte, Anne-Bine; Jensen, Uffe; Nielsen, Finn; Hansen, Thomas
Abstract Background Germline mutations in the succinate dehydrogenase complex genesSDHB, SDHC, andSDHD predispose to pheochromocytomas and paragangliomas. Here, we examine theSDHB, SDHC, andSDHD mutation spectrum in the Danish population by screening of 143 Danish pheochromocytoma and paraganglioma patients. Methods Mutational screening was performed by Sanger sequencing or next-generation sequencing. The frequencies of variants of unknown clinical significance, e.g. intronic, missense, and synonymous variants, were determined using the Exome Aggregation Consortium database, while the significance of missense mutations was predicted byin silico and loss of heterozygosity analysis when possible. Results We report 18 germline variants; nine inSDHB, six inSDHC, and three inSDHD . Of these 18 variants, eight are novel. We classify 12 variants as likely pathogenic/pathogenic, one as likely benign, and five as variants of unknown clinical significance. Conclusions Identifying and classifyingSDHB, SDHC, andSDHD variants present in the Danish population will augment the growing knowledge on variants in these genes and may support future clinical risk assessments.